Duloxetine against symptomatic chemotherapy-induced peripheral neurotoxicity in cancer survivors: a real world, open-label experience. Issue 1 (January 2021) - Velasco, Roser; Besora, Sarah; Argyriou, Andreas A.; Santos, Cristina; Sala, Rosó; Izquierdo, Cristina; Simó, Marta; Gil-Gil, Miguel; Pardo, Beatriz; Jiménez, Laura; Clapés, Victoria; Calvo, Mariona; et al.
Abstract : The objective of this observational study was to evaluate the efficacy and safety of duloxetine in a cohort of 100 cancer survivors with chemotherapy-induced peripheral neurotoxicity (CIPN). CIPN was graded employing the TNSc and the NCI-CTCv4. The Patient Global Impression of Change (PGIC) scale measured the efficacy of duloxetine (1: no benefit; to 7: excellent response). A clinically meaningful response was considered a PGIC > 4. Median age was 62 (29–81) years and 42% were male. CIPN was graded as grades 1, 2 and 3 in 20, 66, and 14% of patients, respectively. Median time to duloxetine initiation was 6 (1–63) months after chemotherapy. Fifty-seven patients early dropped out from duloxetine, due to lack of efficacy (20%) or side effects (37%). Male patients more frequently discontinued duloxetine due to lack of efficacy (35.7 vs. 8.6% P = 0.001). PGIC scores were higher in female patients (4 vs. 1, P = 0.001), taxane-treated patients (4 vs. 1, P = 0.042) and with short-lasting (<6 months) CIPN (4 vs. 1, P = 0.008). Patients with long-lasting CIPN had a higher rate of adverse events (47 vs. 27%, P = 0.038) and discontinuation (54.8 vs. 45.1%, P = 0.023). In the multivariate analysis, female gender and short-lasting CIPN were independently associated with a favorable response to duloxetine. Low tolerability, male gender, and long-lasting CIPN significantly limited duloxetine use in daily practice setting. A minority of cancer survivors with CIPN treated with duloxetine had a meaningful CIPN improvement, and tolerability was overall low. Female gender and short-term CIPN were independently associated with a favorable response to duloxetine. Abstract : Supplemental Digital Content is available in the text.